2013
DOI: 10.1007/s10753-013-9659-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin-2 Level and Genetic Variants on Coronary Artery Disease

Abstract: Inflammation plays important roles in the development of atherosclerosis and coronary artery disease (CAD). Interleukin-2 (IL-2) is a proinflammatory cytokine and induces proliferation of T cells. The aim of the study was to understand the effect of IL-2 on the development of CAD from genetic polymorphism perspective and serum level perspective. IL-2 -330T/G and +114T/G polymorphisms were tested in 692 CAD cases and 723 healthy controls. IL-2 expression of these two polymorphisms was compared. Serum level of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Besides, RES increased the secretion of IL-2 in CD4 + T cells. IL-2 is a proinflammatory cytokine and the level of IL-2 may be close correlated with the development and progression of CVD [51,52]. But IL-2 can induce the development of Tregs, which protect against AS [53].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, RES increased the secretion of IL-2 in CD4 + T cells. IL-2 is a proinflammatory cytokine and the level of IL-2 may be close correlated with the development and progression of CVD [51,52]. But IL-2 can induce the development of Tregs, which protect against AS [53].…”
Section: Discussionmentioning
confidence: 99%
“…IL-2, a pro-inflammatory cytokine, is produced by naive CD4T cells and Th1T cells and induces the proliferation of T cells when CD4 and Th1T cells are stimulated by the appropriate antigen-presenting cell 10. Because leucocytes such as Th1 lymphocytes play an important role in the immune response associated with atherogenesis, serum inflammatory markers with regulatory properties such as IL-2 may also be a critical part of the atherosclerotic process 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…5 Sp. 4 Sen. 3 2 Predicted Group Membership, 3 Sensitivity, 4 Specificity, 5 Positive Predictive Value, 6 Negative Predictive Value, 7 Corrected Classification…”
Section: Table 5 Discriminant Function Parameter and The Effect Of The Combination Of Gene Expression Of Receptor Activator Of Nuclear Famentioning
confidence: 99%
“…Unstable angina (UA) is one of the most common forms of coronary artery disease in which mismatch between demand and supply occurs mainly due to atherogenesis (fatty buildups) and plaque destabilization, as well as rupture, leading to thrombus formation. 1 Several inflammatory mediators play some roles in such pathogenesis 2,3,4,5 such as c-reactive protein (CRP) 2 , interleukin (IL)-2, 4 and IL-6. 2 Some new studies have also shown increased levels of IL-37 and IL-18 in acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%